Clinical and Functional Outcomes by Graft Type in Superior Capsular Reconstruction: A Systematic Review and Meta-analysis. Issue 14 (December 2022) - Lee, Alexander; Farooqi, Ali S.; Novikov, David; Li, Xinning; Kelly, John D.; Parisien, Robert L.
Background: In recent years, superior capsular reconstruction (SCR) has emerged as a promising treatment for massive rotator cuff tears and has been performed with an array of graft options, most commonly dermal allograft and tensor fascia lata (TFL) autograft. Purpose: To compare the clinical outcomes, functional outcomes, and complication rates after SCR performed with dermal allograft, TFL autograft, long head of the biceps tendon (LHBT) autograft, and porcine xenograft. Study Design: Meta-analysis; Level of evidence, 4. Methods: PubMed, Cochrane Library, and Embase were systematically reviewed for studies that enrolled ≥10 patients who underwent SCR and presented clinical outcome data at a minimum follow-up of 12 months. When available, pre- and postoperative patient-reported outcome scores and clinical examination data were extracted. Outcome data were then compared by graft type. A meta-analysis was also conducted of graft tear and reoperation rates after SCR with dermal allograft and TFL autograft. Results: Human dermal allograft and TFL autograft were each utilized in 7 studies, LHBT autograft in 2 studies, and porcine xenograft in 1 study. Dermal allograft, TFL autograft, and LHBT autograft demonstrated comparable median (range) postoperative American Shoulder and Elbow Surgeons scores of 85.3 (77.5-89), 88.6 (73.7-94.3), and 82.7 (80-85.4), respectively. The median postoperative pain scores per visual analog scale for dermal allograft, TFL autograft, and LHBT autograft were 0.8, 2.5, and 1.4. Median postoperative forward elevation was 159.0°, 147.0°, 163.8°, and 151.4° for dermal allograft, TFL autograft, LHBT autograft, and porcine xenograft. Meta-analysis demonstrated a comparable pooled graft tear rate between TFL autograft (9%; 95% CI, 4%-16%) and dermal allograft (7%; 95% CI, 2%-13%). Similarly, the pooled reoperation rate was similar for TFL autograft (3%; 95% CI, 0%-7%) and dermal allograft (6%; 95% CI, 2%-12%). Among the 3 studies with pre- and postoperative information on pseudoparalysis, 73 of 76 (96%) patients with an intact/repairable subscapularis had a reversal of their pseudoparalysis after SCR. Conclusion: Dermal allograft, TFL autograft, and LHBT autograft are all suitable options for SCR and demonstrate significant improvements in American Shoulder and Elbow Surgeons score, pain score per visual analog scale, and forward elevation. Moreover, dermal allograft and TFL autograft have comparable rates of graft tear and reoperation.